ISOLATION AND IDENTIFICATION OF TWO STEROLS AND A TRITERPENE FROM DRY FRUITING BODIES OF Ganoderma lucidum CULTIVATED IN COLOMBIA - MORENO, Henry; MARTINEZ M., Alejandro; FUJIMOTO, Yoshinori (Vitae, 2011)
Ganoderma lucidum is a medicinal mushroom belonging to Ganodermataceae family. It is known as “reishi” in Japan and is widely used in traditional Chinese medicine. Reported metabolites include polysaccharides and triterpenoids with different biological activities. In this paper isolation and identification of ergosterol, 5,6-dihydroergosterol and lucidumol-B, are described. These compounds were isolated from methanolic extract of fruiting bodies of Ganoderma lucidum cultivated in Colombia.